2019
DOI: 10.1101/851501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Competitive Inhibition of Cortisol by Prostaglandins at the Ligand Binding Domain of Glucocorticoid Receptors

Abstract: Here, a pathway is shown for the first time indicating competitive inhibition of cortisol by prostaglandins at the critical ligand binding domain of glucocorticoid receptors. This is significant since these materials are widely distributed: glucocorticoid receptors, cortisol and prostaglandins are found in almost every cell and tissue in the human body. In this article, a cooperative relationship is shown between cortisol and prostaglandin results during normative homeostatic conditions, and thus indicates cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…• Molecule Selection: The A-T pairing was selected for the simulations to evaluate the positioning of the third hydrogen bond relative to the corticosteroid molecule. Cortisol was selected for the study because of a prior study that I conducted on its interaction with prostaglandins in producing fevers and symptoms of other diseases [14], of which a molecular basis for this interaction was sought, indicating competitive inhibition of cortisol by prostaglandings [13]. This investigation led to the development of the calcium ions as a differentiated factor between the expression of steroids and non-expression of non-steroidal molecules capable of occupying the ligand binding domain of cortisol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• Molecule Selection: The A-T pairing was selected for the simulations to evaluate the positioning of the third hydrogen bond relative to the corticosteroid molecule. Cortisol was selected for the study because of a prior study that I conducted on its interaction with prostaglandins in producing fevers and symptoms of other diseases [14], of which a molecular basis for this interaction was sought, indicating competitive inhibition of cortisol by prostaglandings [13]. This investigation led to the development of the calcium ions as a differentiated factor between the expression of steroids and non-expression of non-steroidal molecules capable of occupying the ligand binding domain of cortisol.…”
Section: Methodsmentioning
confidence: 99%
“…Some resetting of the initial conditions to different arrangements were made in order to arrive at a reasonable configuration of nucleotides. The cortisol molecule, and later the PGE2 molecule, were coordinated with the ligand binding domain amino acids of the glucocorticoid receptor, as well as two calcium ions, using previously described methods [13]. The cortisol molecule and the positioning of the calcium ions were then extracted from the LBD and placed in close proximity to the DNA molecule.…”
Section: Methodsmentioning
confidence: 99%
“…The optimization routine was utilized to determine the lowest energy state. Using previously described methods [22], the calcium and magnesium ions were coupled to the DNA nucleotides with the steroid hormone.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular modeling indicated that the GR-PGE2 structure was actually at a lower energy state than that of GR-PGE2. The results were documented in the preprint [5].…”
Section: Introductionmentioning
confidence: 99%
“…Through molecular models, it has been shown in [5] that PGE2 can be conformed such that it and cortisol (CORT) will have a similar arrangement of chemical elements 130 and functional groups which would permit equivalent affinity with the LBD of GR. Cells containing GR are found in almost every cell and tissue, but should be particularly relevant to the hypothalamus that is the control site for temperature, and the site for control of the HPA axis in response to cortisol.…”
Section: Introductionmentioning
confidence: 99%